2014
DOI: 10.1111/ddg.12355
|View full text |Cite
|
Sign up to set email alerts
|

Non‐melanoma skin cancer is reduced after switch of immunosuppression to mTOR‐inhibitors in organ transplant recipients

Abstract: Switch of the immunosuppressive regimen to mTOR-inhibitors should be considered for organ transplant recipients suffering from multiple non-melanoma skin cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 39 publications
0
20
0
3
Order By: Relevance
“…No new skin lesions developed after everolimus replaced CNI therapy, over a minimum follow-up of six months. Low rates of recurrence were also reported over a 24-month follow-up period in five transplant recipients (including two kidney transplant patients) by Alter and colleagues after switch from CNI to everolimus [67]. Limited data from heart transplantation also points to a protective effect for everolimus in patients with skin cancers [68] (see “Heart Transplantation”).…”
Section: Kidney Transplantationmentioning
confidence: 92%
“…No new skin lesions developed after everolimus replaced CNI therapy, over a minimum follow-up of six months. Low rates of recurrence were also reported over a 24-month follow-up period in five transplant recipients (including two kidney transplant patients) by Alter and colleagues after switch from CNI to everolimus [67]. Limited data from heart transplantation also points to a protective effect for everolimus in patients with skin cancers [68] (see “Heart Transplantation”).…”
Section: Kidney Transplantationmentioning
confidence: 92%
“…For example, switching patients to sirolimus has been demonstrated to reduce risk of posttransplant skin cancer 44. patient on a specific treatment regime.…”
mentioning
confidence: 99%
“…patient on a specific treatment regime. For example, switching patients to sirolimus has been demonstrated to reduce risk of posttransplant skin cancer 44. The knowledge of a patient's polygenic risk of skin cancer posttransplant could also inform less drastic interventions such as frequency of checks with dermatologists and may also increase a patient's likelihood to take on board lifestyle interventions such as wearing sunscreen and carrying out regular skin checks.…”
mentioning
confidence: 99%
“…When immunosuppressed patients were switched from calcineurin inhibitors to mTOR inhibitors, Alberú et al 38 found that skin cancer rates were three times lower in the mTOR inhibitor group after two years. Alter et al 39 reported a significant decrease of SCC development in SOTRs as early as the first year after changing immunosuppression to mTOR-inhibitors. Furthermore, Gu et al 40 reported that sirolimus has an anti-tumor effect and sirolimus-based immunosuppression decreases rates of both SCC and BCC in kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%